78.4k views
4 votes
Solve for x: 11x+9=6x-1

User Geekley
by
6.3k points

2 Answers

1 vote
I think the answer is x = -2
User Muhabutti
by
5.4k points
6 votes

Answer: 11x+9=6x-1

We simplify the equation to the form, which is simple to understand

11x+9=6x-1

We move all terms containing x to the left and all other terms to the right.

+11x-6x=-1-9

We simplify left and right side of the equation.

+5x=-10

We divide both sides of the equation by 5 to get x.

x=-2

Step-by-step explanation: Hope this helps

User Dmitry Sheiko
by
6.5k points